2023
DOI: 10.14719/pst.2062
|View full text |Cite|
|
Sign up to set email alerts
|

Population of Halocnemum strobilaceum (Pall.)M.Bieb in a Dry Salt Lake of the Central Kyzylkum

Abstract: Halocnemum strobilaceum (Pall.) M. Bieb. is a halophytic desert plant. This plant population is widespread in areas of high salinity of the world, including a Dry Salt Lake of the Central Kyzylkum. Analyzing the environment of the plant root system and the inorganic and organic composition of the soil of dried salt marshes using modern methods is of great importance in explaining the mechanisms of rapid growth and development of H. strobilaceum in areas affected by the stress factor. In the researches, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Such developments have not only scientific but also great practical significance. Information about the importance of some plants in the desert regions of Uzbekistan is recorded in the works of local and foreign authors (16). Knowing the development trends of rangeland plants and their resistance to anthropogenic influences, it is possible to regulate livestock grazing thus keep rangeland ecosystems in a highly productive state (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Such developments have not only scientific but also great practical significance. Information about the importance of some plants in the desert regions of Uzbekistan is recorded in the works of local and foreign authors (16). Knowing the development trends of rangeland plants and their resistance to anthropogenic influences, it is possible to regulate livestock grazing thus keep rangeland ecosystems in a highly productive state (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of infrared spectroscopy, it is possible to develop a chemically reliable, reproducible, and standardizable method for analyzing various systems [11][12][13][14][15][16]. The study of the IR spectra of soil samples from the Karmaninsky district (Khazora) of the Navoi region showed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, it was reported that 675.11 TWh was generated using biomass as a source. These values are notable compared to 1999 when no energy was generated from waste [10,11].…”
Section: Introductionmentioning
confidence: 99%